1998
DOI: 10.1016/s0040-8166(98)80053-0
|View full text |Cite
|
Sign up to set email alerts
|

Culture of mouse spermatogonial stem cells

Abstract: Spermatogenesis occurs within the seminiferous tubules of mammals by a complex process that is highly organized, extremely efficient and very productive. At the foundation of this process is the spermatogonial stem cell that is capable of both self-renewal and production of progeny cells, which undergo differentiation over a period of weeks to months in order to generate mature spermatozoa. It had been thought that germ cells survive only a brief period in culture, generally less than a few weeks. However, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
0
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(148 citation statements)
references
References 28 publications
2
141
0
5
Order By: Relevance
“…Epigenetic control of differentiation and transcription accessibility for genes of different tissues in normal adult stem cells Normal adult tissues contain stem cells that are responsible for regenerating these tissues (Spangrude et al, 1991;Nagano et al, 1998;Gage, 2000;Temple, 2001;Marshman et al, 2002;Alonso and Fuchs, 2003;Kubota et al, 2004;Collins et al, 2005;Shackelton et al, 2006). Adult stem cells reside in specific niches within different issues (Fuchs and Segre, 2000;Calvi et al, 2003;Zhang et al, 2003;Li and Xie, 2005).…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…Epigenetic control of differentiation and transcription accessibility for genes of different tissues in normal adult stem cells Normal adult tissues contain stem cells that are responsible for regenerating these tissues (Spangrude et al, 1991;Nagano et al, 1998;Gage, 2000;Temple, 2001;Marshman et al, 2002;Alonso and Fuchs, 2003;Kubota et al, 2004;Collins et al, 2005;Shackelton et al, 2006). Adult stem cells reside in specific niches within different issues (Fuchs and Segre, 2000;Calvi et al, 2003;Zhang et al, 2003;Li and Xie, 2005).…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…It was first reported that SSCs can be in vitro cultured for months by Nagano et al (1998). The same group later suggested the addition of GDNF is important to short-term in vitro maintenance of SSCs (Nagano et al, 2003).…”
Section: In Vitro Culture Of Sscsmentioning
confidence: 99%
“…The co-culture of SSCs with monolayers of other cell types as mitotically inactivated murine embryonic fibroblasts (MEF) or STO feeder cells (Nagano et al, 1998) are still discussible, presenting different results so far. MEF is widely used in in vitro culture of embryonic stem cells (Evans & Kaufman, 1981) and has been applied as feeder cells to murine SSCs cultures (Kanatsu-Shinohara et al, 2004a).…”
Section: In Vitro Culture Of Sscsmentioning
confidence: 99%
“…However, in domestic animals, little is known about whether gonocytes have stem cell activity during germ cell development. Culture conditions for maintaining germ cells have been established for various species, including the mouse (Nagano et al 1998(Nagano et al , 2003Kubota et al 2004;Kanatsu-Shinohara et al 2005), rat (Hamra et al 2005), hamster (Kanatsu-Shinohara et al 2008a) and rabbit (Kubota et al 2011). However, culture systems are not available for domestic animal species and cell lines, such as embryonic germ (EG) cells in the mouse, have not been established.…”
Section: Introductionmentioning
confidence: 99%